The Challenges of Learning Arabic Listening Skills Using Youtube as a Learning Tool - Azka, Lulu; Hafsoh, Ummi Nur; Ibrahim, Faishol Mahmoud Adam (Alsina : Journal of Arabic Studies, 2024)
This study presents the challenges of learning maharah al-istima' (listening skills) through the use of YouTube as a learning tool. The research employed a quantitative approach with a survey design as its methodological framework. The survey aimed to gather data on students' experiences and perceptions regarding the use of YouTube in learning maharah al-istima' in Arabic. The results revealed several challenges, including the fast-paced speech of native Arabic speakers, unclear dialogue, the presence of unfamiliar vocabulary, auditory difficulties, trouble understanding the material, and a lack of focus during learning. The analysis also explored the psychological impact and student motivation when using this medium. Despite the challenges identified, the potential benefits of YouTube as a learning tool remain substantial. Therefore, further efforts are required to improve accessibility, establish stricter content selection criteria, and implement effective guidance strategies to create a more balanced and productive learning experience.